The Dampak Kebijakan Beras Indonesia: Produksi, Harga, Import dan Kesejahteraan Petani Periode (2004–2024) - Fahmid, Imam Mujahidin; Fahmid, Mirah Midadan; Badrani, Adib Gemilang (Hasanuddin University, 2025)
This study analyzes rice price governance in Indonesia during the administrations of Susilo Bambang Yudhoyono (2004–2014) and Joko Widodo (2014–2024) using a mixed-methods approach that integrates panel data analysis, asymmetric price transmission testing, and comparative policy mapping. The research findings indicate differences in policy orientations: Yudhoyono emphasized producer price protection and import restrictions, which preserved the Farmer's Exchange Rate but increased vulnerability to supply shocks, while Widodo prioritized market integration and import flexibility, which dampened short-term volatility but weakened price incentives at the farmer level. The study also identified asymmetric price transmission—domestic prices respond more quickly to global price increases than decreases—and widening marketing margins. The proposed integrative policy package includes adaptive price corridors, rule-based buffer stocks, targeted subsidies, post-harvest efficiency, inter-regional logistics improvements, phased-diversified import strategies, and real-time data dashboards. This approach is deemed capable of improving policy timeliness, enhancing supply chain efficiency, and balancing price stability with farmer welfare.